2021
DOI: 10.1186/s12910-021-00622-6
|View full text |Cite
|
Sign up to set email alerts
|

Normative framework of informed consent in clinical research in Germany, Poland, and Russia

Abstract: Background Biomedical research nowadays is increasingly carried out in multinational and multicenter settings. Due to disparate national regulations on various ethical aspects, such as informed consent, there is the risk of ethical compromises when involving human subjects in research. Although the Declaration of Helsinki is the point of reference for ethical conduct of research on humans, national normative requirements may diverge from its provisions. The aim of this research is to examine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is understandable that clinicians may be hesitant to provide information on the overall study design. There is already a widely acknowledged problem of overburdening patients with information, something that is also recognized in the normative frameworks of the study countries ( 4 ). Informing patients about possible rare side effects may trigger certain effects that can harm them and distort studies, placing physicians in a difficult ethical dilemma concerning the nocebo effect ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is understandable that clinicians may be hesitant to provide information on the overall study design. There is already a widely acknowledged problem of overburdening patients with information, something that is also recognized in the normative frameworks of the study countries ( 4 ). Informing patients about possible rare side effects may trigger certain effects that can harm them and distort studies, placing physicians in a difficult ethical dilemma concerning the nocebo effect ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that despite shared acceptance of the norms listed in the Declaration of Helsinki, there are substantial differences on how Germany and Poland implement ethical norms related to patient protection in the different national laws ( 4 ). Cross-border clinical studies are becoming increasingly common, with a substantial increase in studies carried out in countries in of Central and Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…While our focus here is primarily on ethical frameworks within United States and European Union, and it is beyond the present scope to canvas the complexities of consent across all regions and jurisdictions, it is important to note that approaches to informed consent in and across other regions are highly varied. Lacunae in regulatory standards of informed consent and research ethics in some regions underscore a significant need for global harmonization of approaches to informed consent to protect research participants [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Less developed regulatory oversight in some regions has contributed to a trend of “outsourcing” of global clinical trials to jurisdictions where clinical-trial conduct is perceived to be less burdensome, including areas of Eastern Europe, China, India South America, and elsewhere [ 26 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Preserving Patient Autonomy In Clinical Trials Involving Per...mentioning
confidence: 99%